The Use of Question Cards Techniques to Improve Students’ Speaking Ability at Class VII of Muhammadiyah Junior High School of Mataram - Humairaa Humaira; Isnainib isnaini; Hidayati Hidayati; Rima Rahmaniah; Irwandi Irwandi (Muhammadiyah University of Mataram, 2021)
This study aims at determining the effectiveness of using